2010
DOI: 10.1111/j.1755-5922.2010.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in Cardiovascular Prevention: Lessons from Studies on Endothelial Function

Abstract: An “unhealthy” diet is considered as a main cause of increased atherosclerotic cardiovascular disease in the industrialized countries. There is a substantial interest in the potential cardiovascular protective effects of “nutraceuticals,” that is food‐derived substances that exert beneficial health effects. The correct understanding of cardiovascular effects of these compounds will have important implications for cardiovascular prevention strategies. Endothelial dysfunction is thought to play an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 137 publications
(136 reference statements)
0
45
0
Order By: Relevance
“…Several intervention studies have suggested that the consumption of flavonoid-rich foods such as tea, red wine, cocoa and soya can improve endothelial function in patients with manifest cardiovascular and cerebrovascular disease as well as in healthy volunteers with or without cardiovascular risk factors [Vita, 2005;Zuchi et al 2010]. Teragawa and colleagues offered an overview of the studies investigating the effect of isoflavone supplementation, using soy protein isolates and isoflavone extract, on endothelial function, as determined by assessing brachial FMD [Teragawa et al 2008].…”
Section: Endothelial Functionmentioning
confidence: 99%
“…Several intervention studies have suggested that the consumption of flavonoid-rich foods such as tea, red wine, cocoa and soya can improve endothelial function in patients with manifest cardiovascular and cerebrovascular disease as well as in healthy volunteers with or without cardiovascular risk factors [Vita, 2005;Zuchi et al 2010]. Teragawa and colleagues offered an overview of the studies investigating the effect of isoflavone supplementation, using soy protein isolates and isoflavone extract, on endothelial function, as determined by assessing brachial FMD [Teragawa et al 2008].…”
Section: Endothelial Functionmentioning
confidence: 99%
“…In particular, the Mediterranean diet, which may be considered on top of the list, can improve the overall outcome and prognosis of the general population by reducing major cardiovascular risk events (myocardial infarction, stroke, or death from cardiovascular causes) rates (Estruch et al, 2013). This positive action may be related to several mechanisms such as endothelial function amelioration (Zuchi et al, 2010), atherosclerosis burden reduction (Badimon, Vilahur, & Padro, 2010), antithrombotic activities (Chakrabarti & Freedman, 2010), decreases in diabetes and metabolic syndrome incidence and evolution (Davì, Santilli, & Patrono, 2010) and improving dyslipidaemia (Houston, 2012) via lipid metabolism mechanisms (such as improving paraoxonase activities) (Rahimi-Ardabili et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that certain natural products can influence the aetiology, progression and treatment of CVD (Osadolor et al, 2005;Amadou et al, 2009;Zuchi et al, 2010;Sahebkar, 2013) and this may occur by modifying risk factors such as obesity, dyslipidaemia as well as factors involved in systemic inflammation, oxidative stress and thrombosis (Parikh et al, 2005;Napoli et al, 2007). The role of dietary fat in health has been under intensive research during the past decades (Ursula et al, 2014).…”
Section: Introductionmentioning
confidence: 99%